Une connaissance d’amour. Note de théologie sur l’édition critico-historique de « Chemin » (II) / A Knowledge of Love. Theological Reflection on the Critical-Historical Edition of “The Way” (II) - Guillaume Derville (Studia et Documenta)
Based on the critical-historical edition of “The Way”, the first part of this article endeavoured to get closer to the inspired and empathetic book of Saint Josemaria. The charismatic and existential origin of The Way was highlighted and a case was made for a Christological reading. In the second part, G. Derville mentions some theological contributions of Saint Josemaría with regard to the Mystery of Christ, such as: the paternal love of God and divine filiation, contemplation in the middle of the world and professional work, the secular dimension of the apostolate. Here we have a science of God which is that of the saints: The Wisdom of the Love.